Perovskite solar cells based on small molecule hole transporting materials. Issue 36 (28th September 2015) - Swetha, T.; Singh, Surya Prakash
<x xml:space="preserve">Abstract</x> The hole transporting materials in perovskite solar cells have received significant attention in recent years as a promising materials capable of developing high performance photovoltaic devices at low cost.